2022
DOI: 10.3390/nu14173668
|View full text |Cite
|
Sign up to set email alerts
|

Aquilaria crassna Leaf Extract Ameliorates Glucose-Induced Neurotoxicity In Vitro and Improves Lifespan in Caenorhabditis elegans

Abstract: Hyperglycemia is one of the important causes of neurodegenerative disorders and aging. Aquilaria crassna Pierre ex Lec (AC) has been widely used to relieve various health ailments. However, the neuroprotective and anti-aging effects against high glucose induction have not been investigated. This study aimed to investigate the effects of hexane extract of AC leaves (ACH) in vitro using human neuroblastoma SH-SY5Y cells and in vivo using nematode Caenorhabditis elegans. SH-SY5Y cells and C. elegans were pre-expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…But these effects were observed in a low frequency in Madhugrit treated groups. Similar attenuation of high glucose-induced reduction in brood size is reported after treatment of worms with leaves of Aquilaria crassna (agarwood) ( 78 ). Secondly, we observed that high levels of glucose accumulation in the nematode promoted lipogenesis and enhanced triglyceride formation which was visually inspected by Nile red staining.…”
Section: Discussionsupporting
confidence: 71%
“…But these effects were observed in a low frequency in Madhugrit treated groups. Similar attenuation of high glucose-induced reduction in brood size is reported after treatment of worms with leaves of Aquilaria crassna (agarwood) ( 78 ). Secondly, we observed that high levels of glucose accumulation in the nematode promoted lipogenesis and enhanced triglyceride formation which was visually inspected by Nile red staining.…”
Section: Discussionsupporting
confidence: 71%
“…33 A. crassna leaf extracts have been demonstrated to ameliorate glucose-Induced neurotoxicity in vitro. 34 Our unpublished experimental data also indicate that both leaf and agarwood extracts of A. crassna can exert protective effects against D-galactose induced neurotoxicity in mouse hippocampal HT-22 cell line.…”
Section: Introductionmentioning
confidence: 68%
“…35 Limited number of in vitro experiments have shown that the leaves, stem, and agarwood of Aquilaria plants, among other plant parts, exhibit neuroprotective properties. 27,28,30,32,33,46 Scientific investigation into the phytochemical components of agarwood is still quite limited because of the high industrial demand and loss of its natural resources. Therefore, it is crucial to carry out additional research investigations to develop premium goods and medications using agarwood's beneficial phytochemical components.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the high concentration of glucose (50 mM) in C. elegans can reduce body size and brood size of adult worms [ 43 ]. Our transcript analysis suggests that the reproduction and development of HGI C. elegans can be improved by Nar ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…The TGF-β pathway plays a leading role in regulating C. elegans ’ body length and width [ 59 ]. Previous studies have shown that the body length and width of HGI worms are smaller than that of control worms as larvae [ 43 ]. However, the regulation of TGF-β by Nar might allow for the HGI worm to recover its body length to some extent, resulting in the body length of the Nar treatment group on day 2 being longer than that of the HGI treatment group.…”
Section: Discussionmentioning
confidence: 99%